Experimental characterization of a solid oxide fuel cell coupled to a steam-driven micro anode off-gas recirculation fan. (15th March 2020) - Wagner, Patrick Hubert; Wuillemin, Zacharie; Constantin, David; Diethelm, Stefan; Van herle, Jan; Schiffmann, Jürg
Graphical abstract: Highlights: First realized SOFC system with steam-driven anode off-gas recirculation fan. Design of a novel oil-free and durable recirculation fan with gas film bearings. Propulsion with steam turbine leads to explosion-proof and efficient fan operation. One of the smallest steam turbines tested with a tip diameter of 15 mm. Reliable method of measuring recirculation ratios with a double Venturi nozzle. Abstract: While the global fuel utilization of solid oxide fuel cells (SOFCs) is limited by the stack aging rate, the fuel excess is typically used in a burner, and thus limiting the system electrical efficiency. Further, natural-gas-fueled SOFCs require treated water for the steam reforming process, which increases operational cost. Here, we introduce a novel micro anode off-gas recirculation fan that is driven by a partial-admission (21%) and low-reaction (15%) steam turbine with a tip diameter of 15 mm. The 30 W turbine is propelled by pressurized steam, which is generated from the excess stack heat. The shaft runs on dynamic steam-lubricated bearings and rotates up to 175 krpm. For a global fuel utilization of 75% and a constant fuel mass flow rate, the electrical gross DC efficiency based on the lower heating value was improved from 52 % to 57 % with the anode off-gas recirculation, while the local fuel utilization decreased from 75% to 61%, which is expected to significantly increase stack lifetime. For a global fuel utilization of 85%, gross efficiencies of 66% in part load (4.5 kWe ) and 61% in full load (6.3 kWe ) were achieved with the anode off-gas recirculation. The results suggest that the steam-driven anode off-gas recirculation can achieve a neutral water consumption.